2012
DOI: 10.1021/jm300981b
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylphosphonates Control Tumor Cell Proliferation and Dissemination by Simultaneously Inhibiting Carbonic Anhydrase IX and Matrix Metalloproteinase-2. Toward Nontoxic Chemotherapy Targeting Tumor Microenvironment

Abstract: Carbamoylphosphonates (CPOs) have been identified as inhibitors of matrix metalloproteinases (MMPs) and as orally active, bioavailable, and safe antimetastatic agents. In this article, we focus on the direct antitumor activity of the CPOs. We discovered that CPOs also inhibit carbonic anhydrases (CAs), especially the IX and XII isoforms identified as cancer promoting factors. Thus, CPOs can be regarded as novel nontoxic drug candidates for tumor microenvironment targeted chemotherapy acting by two synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
2
22
0
2
Order By: Relevance
“…This is an extension of recently reported research, which showed that CPOs n ¼ 5, 6 -previously recognized in vivo as active anti-metastatic matrix metallo-proteinase (MMP) inhibitors [16][17][18] -also act as CA inhibitors 15 . Matrix metalloproteinases (MMPs) are a family of about 26 zinc endopeptidases, which collectively have the capacity to degrade all the major components of the extracellular matrix.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is an extension of recently reported research, which showed that CPOs n ¼ 5, 6 -previously recognized in vivo as active anti-metastatic matrix metallo-proteinase (MMP) inhibitors [16][17][18] -also act as CA inhibitors 15 . Matrix metalloproteinases (MMPs) are a family of about 26 zinc endopeptidases, which collectively have the capacity to degrade all the major components of the extracellular matrix.…”
Section: Introductionsupporting
confidence: 69%
“…MMPs' and CAs' inhibitory constants have been determined as previously described, respectively 15,18 .…”
Section: Inhibitor Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…boronic acids, phosphates and phosphonates, but yielded no in vivo active compounds. 78 As can be seen in Table 17.1, compound 11 is too short to inhibit ATX, but 12 (JS-403) is a potent inhibitor of ATX. Previous work indicated that water solubility for an inhibitor is not enough, because neutral molecules can partition between two phases resulting in inefficient inhibition.…”
Section: Carbamoylphosphonates: Inhibitors Of Extracellular Zinc-enzymesmentioning
confidence: 99%
“…The family of MMPs, discovered decades ago, does not need that much introduction in view of the worldwide (unsuccessful) activity to discover useful inhibitors , not counting our series of recently published carbamoylphosphonate (CPO) MMP inhibitors and one article of CPO CAs .…”
Section: Introductionmentioning
confidence: 99%